Penerapan Model Think Pair Share dalam Meningkatkan Proses Belajar Siswa pada Pembelajaran Bahasa Indonesia - Ferli, Darmi; Ilmi, Nur; S. Pasinggi, Yonathan (STKIP Andi Matappa Pangkep, 2024)
The problem in this study is the low learning outcomes of fourth grade students. The problem in this study is how the implementation of the Think Pair Share learning model in improving the learning process of students in Indonesian language subjects in Class IV UPT SDN 79 Pinrang. This research is a class action research (PTK) which aims to determine the process and learning outcomes of Indonesian language in grade IV students and to determine the improvement of learning outcomes in learning about the health of my body in grade IV with the application of the Think Pair Share learning model. The approach used in this research is a Translated with DeepL.com (free version) qualitative approach. Data collection techniques used in this study were observation, tests and documentation. The subjects of this study were 1 class teacher and 14 students. The research was conducted in two cycles. In the cycle the research results on the learning process were at sufficient qualification (C) and the learning test results were at sufficient qualification (C). Cycle II research results in the learning process are in good qualifications (B) and learning test results are in good qualifications (B).